(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
Study Goals: From the perspective of students in the University of Tikrit’s Media Department, this study seeks to determine the extent of media coverage provided by both Iraqi and Gulf sports channels. Additionally, it seeks to comprehend the role that Iraqi channels played in covering the 25th Arabian Gulf Cup in comparison to that of Gulf channels. To get at the study’s conclusions, the researcher constructed scales for the media coverage of Gulf and Iraqi channels using the descriptive method in conjunction with survey and correlational methodologies. The researcher came to the following results and suggestions: Conclusions: - Gulf sports media contributes to the public’s increased passion among individuals. - Gulf channels reinforce beneficial features among students and the community. - The predisposition to watch Iraqi stations is poor since they highlight uninteresting subjects for their viewers